PENGARUH MINAT BELAJAR DALAM PEMBELAJARAN BERBASIS VIRTUAL DI MASA PANDEMI COVID-19 TERHADAP KEMAMPUAN KOMUNIKASI STATISTIK MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP USI PEMATANGSIANTAR - Wilson Sitopu, Joni (Jurnal Metabio, 2021)
The purpose of this study is to determine the Effect of Learning Interest in Virtual-Based Learning During the Covid-19 Pandemic on the Statistical Communication Skills of Students in the Biology Education Study Program, FKIP USI Pematangsiantar, Academic Year 2020/2021. This type of research is descriptive quantitative with conclusions drawn through statistical analysis. The population in this study were all fifth-semester students of the Biology Education Study Program, FKIP USI Pematangsiantar, Academic Year 2020/2021. The sample of all fifth-semester students was 30 people (total sample). The required data were obtained through questionnaires and documentation. The previous questionnaire was tested for data normality and data homogeneity. The data analysis techniques used were multiple linear regression analysis, t-test, R2 test, F-test. The results of the regression analysis obtained a linear regression equation: Ŷ = 94.075 X - 0.127. Based on the linear regression analysis (F-test), F count (0.769) > Fsig. (0.388b), it can be concluded that the linear regression direction coefficient is significant, with a correlation coefficient contribution of 0.163, resulting in a determination coefficient of 2.67%, a very low correlation.